1991
DOI: 10.1182/blood.v78.9.2211.bloodjournal7892211
|View full text |Cite
|
Sign up to set email alerts
|

Diamond-Blackfan anemia: heterogenous response of hematopoietic progenitor cells in vitro to the protein product of the steel locus

Abstract: Diamond-Blackfan anemia is a congenital disorder of erythropoiesis in humans, characterized by a macrocytic anemia often associated with physical anomalies. Mutations at either the W or Steel loci in the mouse also leads to a severe macrocytic anemia, as well as other developmental abnormalities. The W locus encodes the proto-oncogene c- kit, a member of the receptor tyrosine kinase family, while the Steel locus encodes a potent hematopoietic growth factor that is the ligand for c-kit. Growth of clonogenic mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 0 publications
3
16
0
1
Order By: Relevance
“…In vitro analysis with haemopoietic growth factors has demonstrated varying levels of erythroid response, despite absent erythroid maturation i n vivo (Freedman et al, 1976;Nathan et al, 1978;Halperin et al, 1989;Olivieri et al, 1991b;Abkowitz et al, 1991;Alter et al, 1992). Most work has centred on simple unfractionated marrow mononuclear cells, although the few studies on partially purified populations have c o n k e d the location of the defect in DBA to be in the early erythroid precursors (Tsai et al, 1989;Bagnara et al, 1991).…”
mentioning
confidence: 99%
“…In vitro analysis with haemopoietic growth factors has demonstrated varying levels of erythroid response, despite absent erythroid maturation i n vivo (Freedman et al, 1976;Nathan et al, 1978;Halperin et al, 1989;Olivieri et al, 1991b;Abkowitz et al, 1991;Alter et al, 1992). Most work has centred on simple unfractionated marrow mononuclear cells, although the few studies on partially purified populations have c o n k e d the location of the defect in DBA to be in the early erythroid precursors (Tsai et al, 1989;Bagnara et al, 1991).…”
mentioning
confidence: 99%
“…Various reports have shown using in vitro studies that IL-3 ( EPO) increases BFU-E numbers in DBA BMMC Abkowitz et al, 1991;Bagnara et al, 1991;Lipton et al, 1986;Olivieri et al, 1991). Our studies have shown that only a small proportion show reasonable increases in erythroid colonies with addition of SCF being the better option (in vitro) for normalizing colony numbers (McGuckin et al, 1995a).…”
Section: Discussionmentioning
confidence: 51%
“…These results provided further evidence for cellular heterogeneity underlying the pathogenesis of DBA and raised the possibility that there may be more than one underlying molecular basis for the disease. No gross abnormalities in the genetic structure of either the c-kit or Steel loci were identified using Southern analyses, and gene sequencing studies that were subsequently performed did not disclose mutations in c-kit or Steel loci [13,25,261. The seemingly normal response in culture of the progenitor cells from some DBA patients to Steel factor with or without the addition of IL-3 raised the possibility of using this novel growth factor as a therapeutic agent in DBA.…”
Section: Phurmacologic Modularion Of Dba Colony Growthmentioning
confidence: 98%
“…In vitro studies with IL-3 were recently extended to examine the effect of Steel factor, alone and in combination with IL-3, on DBA erythroid colony growth [13,[22][23][24]. Three patterns of in vitro marrow response to IL-3 and/or Steel were observed among 10 DBA patients in the Toronto series: those that responded quantitatively and qualitatively almost as well as cells from normal marrow, those that responded at an intermediate level, and those that did not respond at aII [13].…”
Section: Phurmacologic Modularion Of Dba Colony Growthmentioning
confidence: 99%